1997
DOI: 10.1002/(sici)1097-0215(19970304)70:5<530::aid-ijc7>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin receptor subtypes sst1, sst2, sst3 and sst5expression in human pituitary, gastroentero-pancreatic and mammary tumors

Abstract: Using in situ hybridization techniques with selective oligoprobes, the gene expression of sst 1 , sst 2 , sst 3 and sst 5 was studied in a series of 32 human pituitary adenomas, 28 breast tumors and 21 endocrine gastroentero-pancreatic tumors, shown to express somatostatin receptors to variable extents. In most of these tumors the sst 2 receptor subtype was abundantly expressed, even though a significant number of pituitary adenomas, breast and gastroentero-pancreatic tumors expressed sst 1 and/or sst 3 as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(48 citation statements)
references
References 19 publications
2
46
0
Order By: Relevance
“…a In mixed GH+PRL adenomas b Only in 50% of tumors c mRNA expression in less than 20% of analyzed tumors each receptor were selected. All four compounds displayed an very high affinity for sst2 (IC 50 10-100 pmol/L). In the six tumors treated with these compounds, in cell culture, GH secretion was suppressed with an EC 50 significantly lower than that achieved with octreotide (1 to 10 pmol/L vs. 80 pmol/L).…”
Section: The Dopamine-somatostatin Hybrid Molecules In Pituitary Adenmentioning
confidence: 99%
“…a In mixed GH+PRL adenomas b Only in 50% of tumors c mRNA expression in less than 20% of analyzed tumors each receptor were selected. All four compounds displayed an very high affinity for sst2 (IC 50 10-100 pmol/L). In the six tumors treated with these compounds, in cell culture, GH secretion was suppressed with an EC 50 significantly lower than that achieved with octreotide (1 to 10 pmol/L vs. 80 pmol/L).…”
Section: The Dopamine-somatostatin Hybrid Molecules In Pituitary Adenmentioning
confidence: 99%
“…An important common feature of these tumours is the expression of various neuroendocrine markers within the tumour cells and secretion of biologically active peptides and amines, which causes symptoms named carcinoid syndrome. Another characteristic feature of these tumours is the overexpression of somatostatin receptors (SSTR) [2]. Up to now five different SSTR (SSTR1-5) subtypes have been identified and NETs have relatively high expression of SSTR2 which makes them ideal targets for functional imaging with radiolabelled somatostatin (SST) analogues and radionuclide therapy [3].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the presence of SSTRs in a large variety of tumors and cancer cell lines [12][13][14][15][16][17][18]. Breast cancers express both SST and SSTRs.…”
Section: Introductionmentioning
confidence: 99%